TRAINING PROGRAMS EVALUATION IN THE KING ABDULAZIZ MEDICAL CITY - Sara Mohammad Alotaibi; Abdulquddus Mohammad (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Training and development programs are an important component of the organization. It is a common practice in the organization to train employees on the basis of job requirements. However, these training programs need to be evaluated every now and then in order to meet the training requirements. This work was done to analyze the training program provided at King Abdulaziz Medical City. This work has focused on the evaluating the effectiveness of the training program and its impact on hospital employees. This work was done based on quantitative research method. The sample population of this work was non-medical staff from King Abdulaziz Medical City. The sample size was 10 employees. Data collection was done using survey questionnaire. The findings of this work have shown that 50% of respondents said they are satisfied with their training and can train others. This has shown how strong the training program is offered by the organization. Furthermore, the results have shown that all respondents agree that they are satisfied with the method of training and the training program has improved their skills. Moreover, all of the respondents have agreed that they have applied the knowledge that was gained from the training program in their daily work. Hence it is concluded that the training program at King Abdulaziz Medical City is effective and has a positive impact on the employees.